The relationship between cognitive function and high-resolution diffusion tensor MRI of the cingulum bundle in multiple sclerosis. (December 2015) - Koenig, Katherine A; Sakaie, Ken E.; Lowe, Mark J; Lin, Jian; Stone, Lael; Bermel, Robert A; Beall, Erik B; Rao, Stephen M.; Trapp, Bruce D; Phillips, Micheal D
Background: Imaging can provide noninvasive neural markers of disease progression in multiple sclerosis (MS) that are related to behavioral and cognitive symptoms. Past work suggests that diffusion tensor imaging (DTI) provides a measure of white matter pathology, including demyelination and axonal counts. Objectives: In the current study, the authors investigate the relationship of DTI measures in the cingulum bundle to common deficits in MS, including episodic memory, working memory, and information processing speed. Methods: Fifty-seven patients with MS and 17 age- and education-matched controls underwent high-spatial resolution diffusion scans and cognitive testing. Probabilistic tracking was used to generate tracks from the posterior cingulate cortex to the entorhinal cortex. Results: Radial and axial diffusivity values were significantly different between patients and controls ( p < 0.031), and in patients bilateral diffusion measures were significantly related to measures of episodic memory and speed of processing ( p < 0.033). Conclusions: The tractography-based measures of posterior cingulum integrity reported here support further development of DTI as a viable measure of axonal integrity and cognitive function in patients with MS.